Physicochemical analysis of Brazilian spinach grown under doses of urea - Balbino Ferreira , Almecina; Santos da Cruz, Karine; Matos do Nascimento, Matheus; Santos de Lima , Marilene; Souza Torres , Natalia; Carnaúba de Aragão Junior, Antônio (Scientia Agraria Paranaensis, 2021)
The Althernanthera sessilis L. is a non-conventional food plant (PANC) popularly known as Brazilian spinach, rich in minerals and proteins, contributing to human nutrition. In view of the above, the present work aimed to analyze physicochemically Brazilian spinach plants cultivated under doses of nitrogen, in the form of urea. The experiment was carried out at the Experimental Garden of the Universidade Federal do Acre (UFAC), from November 25, 2017 to February 3, 2018 and the laboratory analyzes were carried out at the Unidade de Tecnologia de Alimentos (UTAL/UFAC). The delimitation used was completely randomized, containing 4 treatments (0; 1.5; 3.0 and 5.0 g), five replications and one plant per replication. The vegetative material was obtained in Porto Velho (RO) and the seedlings obtained by cuttings were cultivated in 500 mL polyethylene cups for 15 days and then transferred to pots with a capacity of 9 L. On February 3, leaves and stems of the plant were collected and analyzes were performed on a wet basis, except ash, such as pH, titratable acidity, ascorbic acid, soluble solids and proteins. Significant differences were observed for pH, titratable acidity, ascorbic acid and proteins and a linear increase of the contents with the increase of the urea dose. Nitrogen fertilization up to a dose of 5 g was efficient for the variables of titratable acidity, proteins and ascorbic acid. The highest dose of urea provided an increase of about 24% in protein content, however, even without fertilization, Brazilian spinach showed great potential in terms of protein content, being able to be consumed to supply part of the protein demand.